Altered mitochondrial functioning induced by preoperative fasting may underlie protection against renal ischemia/reperfusion injury. Issue 1 (14th November 2012) - Verweij, Mariëlle; Sluiter, Wim; van den Engel, Sandra; Jansen, Eugène; IJzermans, Jan N.M.; de Bruin, Ron W.F.
Abstract We reported previously that the robust protection against renal ischemia/reperfusion (I/R) injury in mice by fasting was largely initiated before the induction of renal I/R. In addition, we found that preoperative fasting downregulated the gene expression levels of complexes I, IV, and V of the mitochondrial oxidative phosphorylation (OXPHOS) system, while it did not change those of complexes II and III. Hence, we now investigated the effect of 3 days of fasting on the functioning of renal mitochondria in order to better understand our previous findings. Fasting did not affect mitochondrial density. Surprisingly, fasting significantly increased the protein expression of complex II of the mitochondrial OXPHOS system by 19%. Complex II‐driven state 3 respiratory activity was significantly reduced by fasting (46%), which could be partially attributed to the significant decrease in the enzyme activity of complex II (16%). Fasting significantly inhibited Ca2+‐dependent mitochondrial permeability transition pore opening that is directly linked to protection against renal I/R injury. The inhibition of the mitochondrial permeability transition pore did not involve the expression of the voltage‐dependent anion channel by fasting. In conclusion, 3 days of fasting clearly induces the inhibition of complex II‐driven mitochondrial respiration state 3 in part by decreasing the amount of functional complex II, and inhibits mitochondrial permeability transition pore opening. This might be a relevant sequence of events that could contribute to the protection of the kidney against I/R injury. J. Cell. Biochem. 114: 230–237, 2012. © 2012 Wiley Periodicals, Inc.